Enhancing Oral Health among Dentistry Students at Sabratha University: An Exploratory Study - Abdalbaset ALZaitouny; Abdurahman Salama; Ibtesam Amer (AlQalam Journal of Medical and Applied Sciences, 2025)
Oral health is an essential part of overall health and greatly influences an individual’s quality of life. Dental students need to have knowledge and personal experience in good oral health practices, as future practitioners. This research focuses on the oral health status of dental students at Sabratha University, Libya. Thus, this study aimed to evaluate the oral health status of some fourth-year dental students at Sabratha University. The study methodology included conducting a cross-sectional survey of 36 students. They were interviewed and clinical examinations were conducted at the university’s dental clinic, and the clinical examinations showed that all students suffered from oral health problems. The results included 100% suffering from dental problems. The results showed that all students had dental problems. while the percentage of students suffering from early dental problems was 35%, and the percentage of students suffering from dental infection problems was 33%. We refer to the study as the percentage of students, 36% of whom suffer from dental caries, and 17% suffer from the problem of parents not paying attention to the child’s teeth. In comparison, 17% of students shared in emphasizing economic difficulties as the main reason for not undergoing dental examinations and treatments. The percentage of 25% of their students was Ltd. has developed advanced dental techniques and practices over the past two decades. Economic difficulties that prevent them from performing regular dental examinations were 17%, while the percentage of students noticing the limitations of advanced dental techniques reached 78%. Thus, the study recommends the need to organize periodic awareness programs for students and their families about the importance of oral health, provide subsidized or free dental services to students, work to update university clinics with the latest technologies, and train students to use them. تُعد صحة الفم جزءًا أساسيًا من الصحة العامة وتؤثر بشكل كبير على جودة حياة الفرد. من المهم أن يمتلك طلاب طب الأسنان المعرفة والخبرة الشخصية في ممارسات صحة الفم الجيدة، لكونهم ممارسين مستقبليين. يركز هذا البحث على حالة صحة الفم لدى طلاب طب الأسنان في جامعة صبراتة، ليبيا، وبهذا استهدفت هذه الدراسة إلى تقييم حالة صحة الفم لدى بعض طلاب طب الأسنان السنة الرابعة في جامعة صبراتة، حيث شملت منهجية الدراسة بإجراء مسح مقطعي على 36 طالبًا. وتمت مقابلتهم وإجراء فحوصات سريرية لهم في عيادة الأسنان بالجامعة واظهرت الفحوصات السريرية أن جميع الطلاب يعانون من مشاكل في صحة الفم. حيث اظهرت النتائج بانه كافة الطلاب لديهم مشاكل بالأسنان، في حين بلغت نسبة الطلاب الذين يعانون من مشاكل الأسنان المبكرة 35%، ونسبة الطلاب الذين يعانون من مشاكل التهاب في الأسنان 33%، ونشير الدراسة إلى نسبة الطلاب الذين يعانون من مشكلة في تسوس الأسنان بنسبة 36% %، و17% يعانون من مشكلة عدم اهتمام الوالدين بأسنان عند الصغير ، بينما أشترك 17% من طلاب في التأكيد على الصعوبات الاقتصادية كسبب رئيسي في عدم إجراء فحوصات وعلاجات الأسنان، وبلغت نسبة 25% من طلابهم المحدودين لتقنيات وممارسات طب الأسنان المتقدمة على مدى العقدين الماضيين. والصعوبات الاقتصادية التي تمنع إجراء الفحوصات الدورية لأسنانهم 17%، في حين بلغت نسبة الطلاب يلاحظون محدودية التقنيات المتقدمة في طب الاسنان 78%. وبهذا توصي الدراسة بضرورة تنظيم برامج توعية دورية للطلاب وأسرهم حول أهمية صحة الفم وتوفير خدمات طب أسنان مدعومة أو مجانية للطلاب العمل على تحديث عيادات الجامعة بأحدث التقنيات وتدريب الطلاب على استخدامها